POTENSI PURUN SEBAGAI SUMBER DAYA ALAM UNTUK MENDUKUNG KEBIJAKAN EKONOMI LINGKUNGAN - Norlea Norlea; Rosalina Kumalawati (Pelantar Press, 2023)
Purun is a typical wetland plant in South Kalimantan that has ecological, economic, and socio- cultural value. Traditionally, purun is used as a raw material for crafts such as mats, bags, and baskets, which not only have commercial value but also reflect local cultural identity. This study aims to analyze the potential of purun as a natural resource that supports the environmental economy through a literature review. The results show that purun plays an important role in maintaining swamp ecosystems, preventing erosion, storing carbon, and functioning as a phytoremediation agent. From an economic perspective, purun supports community-based creative industries by producing environmentally friendly crafts as an alternative to plastic products. From a socio-cultural perspective, purun contributes to the preservation of traditions, empowering women, and strengthening local identity. However, its development still faces challenges such as limited markets, minimal product innovation, and the threat of land use changes. Therefore, a sustainable economic management strategy is needed to ensure the ecological, economic, and socio-cultural benefits of purun are maintained.